The Capability of Teaching English to Young Learners in SDIT Wahdah Islamiyah Sinjai - Aminah, Sitti; Sabaruddin; Kareba, Andi Muammar; Ishak, Nurkhasanah; Marlina (Universitas Islam Ahmad Dahlan (UIAD), 2023)
This study investigated teachers' and students’ capability to conduct English programs for young SDIT Wahdah Islamiyah Sinjai learners. Therefore, the participants of this study were from two aspects, as mentioned above. There was one level of schools involved in this study. That was elementary school level. The data were collected through the questionnaire and interview and focused on their capability to conduct English at its level. This study showed that students’ capability to learn English was very high even though they often encountered obstacles or difficulties in learning English in class. On the other hand, the teacher's capability was high, although they lacked confidence in using English in the classroom, and it was found that the teacher's background of education became one of the reasons. Moreover, teacher training was conducted to be needed to develop their professionalism. However, they also stated that they still needed to attach that training. Therefore, more professional development training was needed to improve teachers' capability to teach at the elementary level.